Successful resection of growing teratoma syndrome in the abdominal wall with reconstruction using tensor fascia lata muscle flap: A case report and literature review - Miho Iwai; Kaori Yoriki; Kohei Aoyama; Yosuke Tarumi; Hisashi Kataoka; Tetsuya Kokabu; Toshiaki Numajiri; Taisuke Mori (Elsevier, 2023)
While cancer cure is the primary goal, fertility preservation is also a cornerstone of the underlying principle of treatment for ovarian germ cell tumors. Growing teratoma syndrome (GTS) presents with growth of mature teratomas during or after chemotherapy. We report a case of successful treatment of GTS in the anterior abdominal wall involving reconstruction. A 23-year-old woman with a suspected right ovarian mature teratoma with torsion underwent emergency laparoscopically assisted extracorporeal ovarian cystectomy. Histopathological findings revealed a grade 1 immature teratoma. After two months, postoperative α-fetoprotein (AFP) levels increased, and disseminated lesions developed not only in the pelvic cavity but also in the abdominal wound where the tumor had been extracted using an extracorporeal technique at the time of primary surgery. The patient underwent laparoscopic right salpingo-oophorectomy, excision of multiple peritoneal nodules, and biopsy of abdominal wall mass. The left rectus abdominis muscle tumor could not be removed. All of these nodules were diagnosed as metastatic immature teratomas. Although the patient received three cycles of chemotherapy, the residual tumor in the abdominal wall grew remarkably despite post-chemotherapy normalization of AFP levels. Both rectus abdominis muscles involving the residual tumors were removed and reconstructed using a left tensor fascia lata muscle flap. Histopathologically, the residual tumors were identified as mature teratomas with no immature elements, resulting in GTS. The patient got pregnant without the need of fertility treatment and gave birth uneventfully by cesarean section. Thus, reconstruction with a tensor fascia lata muscle flap facilitated complete removal of GTS while preserving fertility.